Effect of “Lalang” (Imperata cylindrica) Extraction on Microorganisms - Nabihah, binti Nordin (Universiti Malaysia Sarawak (UNIMAS), 2015)
Knowledge on the control method of Imperata cylindrica is sparse although this species is not rare to be seen. This plant has a wide genetic variability therefore it can adapts in a wide range of ecological. It has been known as one of the worse weeds throughout the world. I. cylindrica usually leaves in fertile soil. The scope of this study was to evaluate the effect of I. cylindrica extracts on microorganisms and to identify the chemical compounds in “lalang” extracts. This experiment was conducted using the extraction mixture with media method. The whole plant was used to prepare the extraction; leaf crude extract and rhizome crude extract. The extraction used in this study is ethanol extract and there were four concentrations; 0 %, 1 %, 5 % and 10 % used to inhibit the microorganisms growth rate. The extract was mixed and solidified with the media. The microorganisms tested were Fusarium oxysporum, Fusarium solani, Colletotrichum sp. and Sclerotium sp.. There was inhibitory actions towards all microorganisms except Sclerotium sp.. The major chemical constituents detected through GC analysis were benzyl benzoate (leaf and rhizome extract), n-Butyl myristate (rhizome extract) and hexadecanoic acid (rhizome extract). These compounds were proved can give inhibitory effects towards the microorganisms.